Risks and Security of Internet and Systems : 9th International Conference, CRiSIS 2014, Trento, Italy, August 27-29, 2014, Revised Selected Papers - Lopez, Javier; Ray, Indrajit; Crispo, Bruno; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post- conference proceedings of the Ninth International Conference on Risks and Security of Internet Systems, CRiSIS 2014, held in Trento, Italy, in August 2014. The 13 full papers and 6 short papers presented were selected from 48 submissions. They explore risks and security issues in Internet applications, networks and systems covering topics such as trust, security risks and threats, intrusion detection and prevention, access control and security modeling.
Trust -- Security risks and threats -- Intrusion detection and prevention -- Access control and security modeling.
Keywords: Computer security; Computer Communication Networks; Information Systems; Software engineering; Data encryption (Computer science).; Systems and Data Security; Computer Communication Networks; Management of Computing and Information Systems; Software Engineering; Information Systems Applications (incl. Internet).; Cryptology